Colour stability comparison between ormocer nanohybrid composites and udma-based nanocomposites after immersion in coffee – Experimental study - Julia Elizabeth Guy; Tawfiq Hijazi Alsadi; Susana Muwaquet Rodriguez (Saudi Dental Journal)
Introduction: Colour stability of composite materials is an essential property that greatly influences the longevity of dental restorations. Once in the oral cavity, dental materials must provide a stain resistance ability against environmental exposures, such as coffee. This experimental study compares the colour stability of two composite resin materials with differing nanocompositions. Objectives: Analyze the effect of coffee on the colour stability of nanohybrid composites and nanocomposites. Material and Methods: 40 composites discs were utilized in total, with 20 fabricated of an Ormocer-based nanohybrid composite (Admira Fusion) and 20 of a UDMA-based nanocomposite (Normofill nanoceram) in shade A2. 10 discs of each material were then immersed in coffee or water for 12 days. Colour measurements were taken before and after the staining period using a VITA Easyshade spectrophotometer. The colour difference (ΔE) of both composites was calculated using the CIE L*a*b* values. Results: Both Ormocer-based nanohybrid composites (Admira Fusion) and UDMA-based nanocomposites (Normo fill nanoceram) exhibited a colour change after the 12-day period. The UDMA-based nanocomposite (Normo fill nanoceram) exhibited significantly more discolouration compared to the Ormocer-based nanohybrid composite (Admira Fusion). Conclusions: Overall, there was a significant difference in colour generated by immersion in coffee as compared to water. Additionally, the Ormocer-based nanohybrid composite (Admira Fusion) exhibited significantly greater colour stability as compared to the UDMA-based nanocomposite (Normo fill nanoceram).